Evaluating a Future Remote Control Environment with an Experience-Driven Science Fiction Prototype - Kymalainen, Tiina; Perala, Piia; Hakulinen, Jaakko; Heimonen, Tomi; James, Jobin; Pera, Juha (2015 International Conference on Intelligent Environments, 2015)
The case study presented in this paper aimed at discovering opportunities for ambient intelligence and new interaction methods for a future remote crane-operating environment. The theoretical objective was to carry out an experience-driven research project in an industrial work context, and the practical objective was to create and evaluate a future oriented science fiction prototype. The work was carried out in close co-operation with an industrial partner who was a domain expert in the field of crane industry. The aim was to focus on clearly defined user experience goals to which the industrial partner committed. The consequent immediate objective was to focus on two explicit experiences relating to 'Feeling of being motivated' and to 'Sense of community' that were placed at the core of the design investigations. These experiences were deliberated into a science fiction prototype entitled 'Remote operator's day in a future control centre'. The science fiction prototype was further introduced to users by twofold means: as a plain, simple short story and through an interactive experience path. The main contribution of the paper is to demonstrate how an emerging technology research of a new domain may employ science fiction prototyping method as a primary means of experience design investigations.